Study of sea level variation of exclusive economic zone of Malaysia - Omar, Kamaludin; Ses, Sahrum; Naeije, Marc; Mustafar, Mohd. Asrul (2005)
Since a decade, satellite altimetry has demonstrated its capability in measuring temporal change of the global mean sea level with a precision better than 1 mm/year. Here, sea level variation for four areas in Exclusive Economic Zone (EEZ) of Malaysia have been investigated using eleven years of Topex altimetry data. The recently updated environmental and geophysical corrections were applied in altimetry data processing. The analysis of Topex data presented is based on cycle by cycle averages using GOT00.2b and FES2002 ocean tide model. The time series of dynamic sea surface elevation clearly show El NiÃ±o effect on the end of 1997 and sea level rising in EEZ of Malaysia. Linear term of sea level variation for those areas are estimated at a rate between 2.5 â€“ 8.8 mm/year. Comparison results between two ocean tide present that GOT00.2b better than FES2002 for shallow water such as Malacca Strait.